The effect of liquidity on firm value: research and development intensity as moderating variable - Diaz Prasetya Bayu Aji; Andi Kushermanto; Inayah Risqi Alisa (Business, Accounting, and Knowledge Journal, 2024)
This study aims to examine the effect of the liquidity ratio on company value and the influence of research and development (R&D) intensity as a moderating variable. The population used in this study is manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 to 2021. The data used is secondary data from the financial statements of companies. The sampling technique used is purposive sampling, while the analysis technique used is partial least squares structural equation modeling (PLS-SEM). Based on purposive sampling, there were six companies selected for five years, or as many as thirty observations as the sample in this study. This research found that the liquidity ratio has a positive effect on the firm value, and R&D intensity strengthens the relationship between the liquidity ratio and the firm value. Theoretically, this study contributes to signaling theory for the discussion of firm value. Practically, this research can be a consideration for current investors and potential investors to consider the aspect of research and development intensity, particularly when investing in manufacturing companies.